CD34 and BerEP4 Are Helpful to Distinguish Basaloid Tricholemmoma From Basal Cell Carcinoma. (August 2018) - Turnbull, Nicholas; Ghumra, Waseem; Mudaliar, Vivek; Vella, Josefa; Sanders, D. Scott A.; Taibjee, Saleem; Carr, Richard
Abstract : Abstract: Tricholemmoma, a benign follicular neoplasm with outer root sheath differentiation, typically comprises clear or pale cells, and when multiple is pathognomic of Cowden's syndrome. The tumor is probably underrecognized and in basaloid examples can be difficult to distinguish from basal cell carcinoma (BCC). We studied 55 tricholemmomas (including 15 basaloid cases) and compared immunohistochemical profile with nodular BCC from our archives. Basaloid and non–basaloid tricholemmomas had similar staining characteristics. BerEP4 was focally positive (range 10%–20%) in only 3/39 (7.7%) tricholemmomas compared with widespread positivity in BCC (90.8%, 139 of 151 cases with ≥50% tumor area stained). CD34 was expressed, usually focally (median 20%, range 10%–90%), in 52/53 (98.1%) tricholemmomas and was negative in all 21 BCCs stained. EMA staining lacked sensitivity or specificity in differentiating tricholemmoma from BCC. Five or more Merkel cells were found in 7/17 (40.1%) tricholemmomas and 1/23 (4.3%) nodular BCCs studied. In summary, immunohistochemistry is helpful in distinction between tricholemmoma, including difficult basaloid examples (BerEP4 negative or focal, CD34 positive) compared with BCC (BerEP4 widespread in most cases, CD34 negative). The presence of 5 or more Merkel cells is a relatively specific but not a particularly sensitive discriminator.